[Bmim]FeCl4 mediated inhibition and toxicity during anaerobic digestion: Dose-response kinetics, biochar-dependent detoxification and microbial resistance. (15th February 2022) - Li, Jingyi; Yao, Yilin; Shi, Yongsen; Tang, Jingchun; Gadow, Samir Ibrahim; Liu, Rutao; Niu, Qigui
Highlights: The first comprehensive insights of [Bmim]FeCl4 effiecency in anaerobic digestion. The activity of hydrolase/ATPase was stimulated at 0.4 g/L but inhibited at 2.65 g/L. Competitive H-bonding in the activity site of enzyme was revealed by molercule docking. Acetoclastic methanogens exhibited a higher tolerence than H2 -trophic methanogens. Biochar increased α-diversity with detoxification due to surface functional groups. Abstract: [Bmim]FeCl4, or 1‑butyl‑3-methylimidazolium tetrachloroferrate, is a typical ionic liquid (IL). Its recyclable, magnetic, multicomponent, and solvent-free nature makes it a particularly attractive ionic liquid for use in industrial processes. Despite its widespread use, the potential hazards that [Bmim]FeCl4 might pose to the environment, including productive microorganisms, have not been explored. In this study, the dose-response of [Bmim]FeCl4 in anaerobic digestion (AD) was investigated to assess the potential toxification and biochar-dependent detoxification in microbial communities, including enzymatic activity and molecule docking dynamics. Our results showed that methane production (31.52 mLmax /gVS) was sharply inhibited following [Bmim]FeCl4 treatment. Moreover, increasing the dosage of [Bmim]FeCl4 caused more dissolved organic matter (DOM) to be generated. Interestingly, 0.4 g/L of [Bmim]FeCl4 could stimulate the high activity of microbial hydrolase and ATPase. However, a higher concentration of 2.65 g/L prevented these enzymatic processes from continuing. At the cellular level, higher concentration of [Bmim]FeCl4 (>0.4 g/L) increased malondialdehyde (MDA) levels, leading to a higher cell lethal rate and weakening of the secondary structures of protein (especially, the amide I region). At the molecular level, the competitive H-bonding in the active sites caused low activity and consummated more energy. At the community level, structural equation modeling (SEM) revealed that [Bmim]FeCl4 and biochar were the main drivers for microbial community succession. For instance, high [Bmim]FeCl4 (8 g/L) benefited the growth of Clostridium sensu_stricto (from ≤1% to 27%). It is worth mentioning that biochar reversed the inhibition with high α-diversity, which caused a resurgence in the activity of previously inhibited ATPase and hydrolase. H2 -trophic methanogens ( Methanolinea and Methaofastidisoum ) were sensitive to [Bmim]FeCl4 and decreased linearly while acetoclastic methanogens ( Methanosaeta ) were unchanged. These findings were consistent with the short-term activity tests and further verified by functional analysis. Graphic abstract: Image, graphical abstract